2012
DOI: 10.4236/ojpc.2012.21004
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Special Potential Scan Programs for Cyclic Voltammetric Development of Different Nickel Oxide-Hydroxide Species on Ni Based Electrodes

Abstract: Special potential scan programs were designed for cyclic voltammetric development of β-NiOOH or γ-NiOOH/ β-NiOOH mixtures on the surface of nickel or nickel-chromium (80:20) alloy electrodes in NaOH 0.10 M. The programs consisted on changing the anodic or cathodic switching limit to facilitate the chemical reactions taking place either between Ni(II) hydroxides or between Ni(III) oxides-hydroxides. The electrochemical charge density under the oxidative wave, observed at Ni or Ni-Cr electrode surfaces at approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Kim et al [39] also reported that the shift in the Ni 2 + /3 + redox features in the negative direction (> 50 mV) is induced by the presence of Co in the Ni hydrous oxide lattice. In agreement with the previous observations by other groups, [10,38,39] no discernible voltammetry features associated with the Co 2 + /3 + redox couple can be identified for the composite Ni-Co oxide film. Despite of a harmony with previous observations, the precise effect on the catalytic mechanism remains unknown.…”
Section: à2supporting
confidence: 82%
See 1 more Smart Citation
“…Kim et al [39] also reported that the shift in the Ni 2 + /3 + redox features in the negative direction (> 50 mV) is induced by the presence of Co in the Ni hydrous oxide lattice. In agreement with the previous observations by other groups, [10,38,39] no discernible voltammetry features associated with the Co 2 + /3 + redox couple can be identified for the composite Ni-Co oxide film. Despite of a harmony with previous observations, the precise effect on the catalytic mechanism remains unknown.…”
Section: à2supporting
confidence: 82%
“…Marioli and co-workers [38] observed that this negative shift takes place for Ni-Cr binary oxide films, whereas single-component nickel oxide showed only an anodic redox peak shift. Kim et al [39] also reported that the shift in the Ni 2 + /3 + redox features in the negative direction (> 50 mV) is induced by the presence of Co in the Ni hydrous oxide lattice.…”
Section: à2mentioning
confidence: 99%
“…The peak at c.a. +0.45 V vs. Hg/HgO is caused by nickel oxidation [37] and slightly masks the onset of oxygen evolution, which begins at +0.33 V vs. Hg/HgO. For the OER, the Ni/Fe + Pd air electrode outperforms all the other air electrodes in terms of current density.…”
Section: Electrochemical Analysis Of the Mixed Catalyst Oxygen Electrodementioning
confidence: 99%
“…3a). This new wave was ascribed to the reduction of γ-NiOOH [47]. Thus, the charges obtained under cathodic peaks II and III represent the amount of β-NiOOH or γ-NiOOH produced during the positive going potential sweep or anodic polarization during the OER.…”
Section: Sem and Eds Analysis Of Nisn Coatingsmentioning
confidence: 96%